Chapter I ritratti di uomini illustri degli Uffizi dipinti da Carlo Ventura Sacconi, Giovanni Pietro Pollini e Giovanni Berti - Laura (Studi e saggi, 2020)
Documentary investigations conducted at the Florence State Archives contributed to shed light on eighteenth-century efforts to develop the collection of the Uomini Illustri portraits, exhibited along the walls of the Uffizi Gallery. While the original body of works had been commissioned by granduke Cosimo I to Cristofano di Papi dell'Altissimo, who had copied the series held by Paolo Giovio in his villa in Como, the Florentine collection was later enriched by a massive supply of portraits between 1719 and 1733. The desire to complete the Uffizi 'gioviana' series was probably due to Anna Maria Luisa de' Medici and the artist who followed in Cristofano dell'Altissimo's footsteps should be identified in Carlo Ventura Sacconi (1676-1762), who painted 159 portraits of illustrious men. Between 1721 and 1727 the painter also completed the so-called 'serie Aulica', which was displayed - just like the 'gioviana' series - in the corridors of the Florentine Gallery.